Safe Administration of Ipilimumab, Pembrolizumab, and Nivolumab in a Patient with Metastatic Melanoma, Psoriasis, and a Previous Guillain–Barré Syndrome - Cortellini, Alessio (Case Rep Oncol Med, 2018)
BACKGROUND: Patients with autoimmune diseases were not evaluated in clinical trials with immune checkpoint inhibitors (ICIs), since a history of immune disorders, such as Guillain–Barré syndrome (GBS) and psoriasis, is one of the major risk factors for the development of immune-related adverse events (irAEs). This risk cannot be defined; therefore, physicians are called to manage these patients in clinical practice. CASE REPORT: We report the case of a 62-year-old male patient affected by metastatic melanoma, with a history of GBS and psoriasis, and treated with sequential ipilimumab, pembrolizumab, and nivolumab, without significant toxicities. CONCLUSION: This case report supports that although a history of immune disorders is one of the major risk factors for development of irAEs, in some patients, it could be possible to safely administer sequential treatments with ICIs. A proper decision should be made, considering therapeutic options, disease-related risks, and those related to a recurrence of preexisting autoimmune disorders.